A hard carbon negative electrode material based on heteroatom-doped defect graphene and a preparation method thereof

CN122992060APending Publication Date: 2026-10-27SHANG HAI SAI SAN BAO NENG YUAN JI SHU YOU XIAN GONG SI
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202610913642.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-24
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0008]有鉴于此,本发明提供一种缺陷石墨烯改性硬碳负极材料及其制备方法和在电池中的应用,以解决现有硬碳负极首周效率低、SEI膜不稳定以及倍率性能不佳的技术难题

Benefits of technology

1、本发明的首周效率提升,缺陷石墨烯涂层在电池首次充放电时优先与电解液发生反应,形成一层致密、均匀的有机/无机复合SEI膜。该涂层将硬碳表面与电解液隔离开来,大幅减少了裸露硬碳与电解液直接接触所导致的不可逆钠消耗。缺陷石墨烯覆盖在硬碳颗粒表面,首次嵌钠过程中与电解液分解产物反应形成内外双层结构的SEI;由于石墨烯的存在,SEI更加致密且附着牢固,有效降低了首次不可逆容量损失。同时,石墨烯中的杂原子(如N、B等)可以影响和调控SEI的组分比例(例如促进无机成分的生成),从而提高SEI膜的稳定性和离子导电性。在本发明实施例中,经过缺陷石墨烯改性的硬碳负极首周库伦效率可提高至约90%,明显高于未改性硬碳负极约78–80%的水平,在采用常规碳酸酯电解液+2%FEC添加剂的条件下测得。这表明本发明显著减少了首次充放电中的不可逆钠损失。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122992060A_ABST
    Figure CN122992060A_ABST
Patent Text Reader

Abstract

The application discloses a kind of hard carbon negative materials based on heteroatom doped defect graphene and preparation method thereof, comprising: hard carbon particles;And the defect graphene coating layer coated on the surface of the hard carbon particles;The defect graphene coating layer contains structural defects and heteroatom doping.The application is synergized by material surface coating and doping, effectively inhibits the first irreversible reaction, enhances the interface stability and improves the electrode dynamics, realizes the comprehensive improvement of sodium-ion battery negative performance, has outstanding novelty and creativity, and is suitable for the development of high-performance sodium-ion battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of new energy storage technology, and in particular relates to a hard carbon anode material based on heteroatom-doped defect graphene and its preparation method. Background Technology

[0002] The main patent of the Thunderbird Super Battery Platform proposes using graphene materials with controllable defects as a core functional material in novel energy storage devices, and has derived several sub-module inventions based on this. This invention is an extension module of this platform, focusing on the anode field of sodium-ion batteries, and differs in its technical focus from other patent modules within the platform. For example, other patents on the platform involve the preparation of Azopyrene defective graphene and its applications in sensing, catalysis, etc., emphasizing a method for introducing graphene defects through special precursor molecules; other patents focus on graphyne anode materials, studying the performance improvement of another carbon material structure in sodium-ion batteries; and there are patents regarding composite electrode architectures, emphasizing multi-layered material structure design. This invention, however, focuses on the application of defective graphene in the interface regulation of hard carbon anodes in sodium-ion batteries, proposing a unique solution at the material and interface levels, and therefore does not overlap with the aforementioned patents in terms of claims.

[0003] Sodium-ion batteries are considered strong contenders for next-generation energy storage batteries due to their abundant resources and low cost. Among them, hard carbon (amorphous carbon) is one of the most promising anode materials for sodium-ion batteries. Hard carbon has a disordered graphite layer stacking structure and a large interlayer spacing, which can provide a specific capacity of about 250–400 mAh / g. However, hard carbon anodes also have significant drawbacks: their initial irreversible capacity loss is relatively large, and the first-cycle coulombic efficiency is usually only around 70%; at the same time, during repeated sodium insertion / extraction cycles, an unstable solid electrolyte interface film is easily formed at the anode / electrolyte interface, resulting in rapid capacity decay and limited cycle life.

[0004] To address the issues of low initial efficiency and poor interfacial stability in hard carbon anodes, researchers have explored various methods: Firstly, electrolyte formulation optimization is crucial. For example, patent CN106785008A points out that when using traditional carbonate ester solvents, the abundant defects on the surface of hard carbon or graphene anodes undergo a violent and irreversible reaction with the electrolyte, leading to a large consumption of sodium ions during the initial sodium intercalation, forming an unstable SEI film. This results in extremely low initial coulombic efficiency and poor cycle performance. To address this, the patent uses ether compounds as the electrolyte solvent and graphene as the anode material. The result is a more dense and uniform SEI with higher ionic conductivity after the first few charge-discharge cycles, significantly improving the initial coulombic efficiency and cycle / rate performance of sodium-ion batteries. This method demonstrates that changing the electrolyte system can mitigate the side reactions between the electrolyte and surface defects of the anode material. However, simply optimizing the electrolyte does not solve the problem at its core, and changing the electrolyte composition may affect the battery's cost and compatibility.

[0005] Second, pre-sodium treatment. This involves embedding a certain amount of sodium into the negative electrode material before the first charge and discharge cycle to form a stable SEI and reduce initial sodium consumption. CN113178548A proposes a method for pre-sodiuming graphene-based negative electrodes: the negative electrode sheet is contacted with a sodium source reagent before battery assembly to generate an ionicly conductive and electrolyte-insoluble protective SEI film, significantly increasing the first-cycle coulombic efficiency from approximately 78% to 96.8%. This approach constructs the SEI at the electrode level in advance, significantly improving the first-cycle efficiency. However, direct pre-sodium treatment presents challenges such as complex processes and operational safety concerns. Furthermore, the pre-sodium treated electrode may experience performance degradation when exposed to air or stored for extended periods, posing challenges to battery manufacturing processes. Besides pre-sodium treatment, other methods for compensating for initial losses have been reported in the literature, such as adding appropriate amounts of chemical sacrificial additives or performing a constant-voltage charge after assembly to pre-form the SEI. However, these methods often suffer from byproduct generation or complex operations.

[0006] Thirdly, there is the structural design and surface modification of carbon materials. This approach focuses on the material itself to improve the storage activity and interfacial stability of hard carbon anodes for sodium ions. For example, appropriate defect structures can be introduced by adjusting carbonization conditions, or heteroatom doping can be applied to the carbon material. CN114275762A reports a lignin-based nitrogen-doped hard carbon material: approximately 2 at% nitrogen is introduced into the hard carbon to increase the defect concentration and interlayer spacing, thereby increasing the number of active sites for sodium ions. This material maintains a capacity retention of 95.6% after 200 cycles at a current density of 0.2 A / g, and still retains a capacity of 91 mAh / g at a high rate of 800 mA / g, demonstrating high specific capacity and good rate performance. Nitrogen doping increases the number of defect sites inside the carbon material and improves electronic conductivity; the synergistic contribution of both improves the initial capacity and rate performance of the hard carbon. For example, the use of carbon-graphene composite structures has also proven effective: CN108777303A combines biomass hard carbon with graphene oxide via a sol-gel method, resulting in a hard carbon / graphene anode that retains a specific capacity of approximately 210 mAh / g after 1000 cycles at a current density of 1 A / g. The introduction of graphene constructs a conductive network for the hard carbon particles and provides flexible support, significantly improving structural stability and long cycle life. Furthermore, studies have introduced nanoparticles or oxide coatings onto the surface of carbon-based materials to enhance interfacial stability. For instance, CN109686961A prepared a defect-rich sodium titanate / graphene composite anode by in-situ deposition of TiO2 and its conversion to sodium titanate: it maintained excellent performance at ultra-high rates, with a capacity retention of up to 90% after tens of thousands of cycles, demonstrating that introducing defects and inorganic components into carbon materials can effectively improve rate performance and ultra-long cycle stability.

[0007] In summary, existing technologies have improved the interfacial behavior and electrochemical performance of hard carbon anodes in sodium-ion batteries to some extent through various approaches, including electrolyte optimization, pre-sodiumization, heteroatom doping, carbon-graphene composites, and interfacial coatings. However, these methods each have limitations: simply changing the electrolyte does not eliminate interfacial side reactions from within the material, limiting the effectiveness and potentially introducing new compatibility issues; the pre-sodiumization method is complex and poses safety hazards, restricting large-scale application; single doping or simple composites often fail to simultaneously improve both initial efficiency and long cycle life. This invention addresses these unresolved key issues by proposing a comprehensive modification strategy that organically combines surface coating and internal doping. Compared to other patents on the platform that focus on different fields or material systems, this invention focuses on hard carbon anodes, utilizing the synergistic effect of defective graphene coatings and heteroatom doping to simultaneously optimize both the material interface and structure. This effectively suppresses the initial irreversible reaction and enhances ion transport channels, achieving a comprehensive improvement in the interfacial stability and structural performance of the hard carbon anode. This innovative approach addresses the shortcomings of existing single modification methods and is expected to significantly improve the overall performance of sodium-ion battery anodes. Summary of the Invention

[0008] In view of this, the present invention provides a defective graphene-modified hard carbon anode material, its preparation method, and its application in batteries, to solve the technical problems of low initial cycle efficiency, unstable SEI film, and poor rate performance of existing hard carbon anodes. The technical solution of the present invention can significantly improve the initial coulombic efficiency and long-term cycle stability of sodium-ion battery anodes, while also maintaining performance at high rates.

[0009] To achieve the above objectives, the technical solution of the present invention is implemented as follows: A hard carbon anode material based on heteroatom-doped defect graphene, comprising: hard carbon particles; And the defective graphene coating layer covering the surface of the hard carbon particles; The defective graphene coating contains structural defects and heteroatom doping.

[0010] This invention constructs a graphene coating rich in defects on the surface of a hard carbon anode and, combined with a heteroatom doping strategy, achieves stabilization and structural optimization of the anode interface. In summary, a method for applying defective graphene in the interface control and structural optimization of sodium-ion battery anodes includes: coating or doping a graphene material with defective structures onto or introducing it into the anode substrate, thereby forming a stable conductive protective layer on the anode surface and providing additional sodium-ion storage active sites inside / at the anode. The anode substrate is preferably a hard carbon material, but not limited to it; in other embodiments, the substrate can also be a soft carbon material or even a metallic sodium anode. The method of this invention is equally applicable to these anodes, and by constructing a defective graphene coating on its surface, dendrite growth and interfacial side reactions can be suppressed, improving the safety and stability of the battery. The defective graphene material is preferably derived from the reduction product of graphene oxide or graphene modified by heteroatom doping. This defective graphene contains a large number of structural defects and bonded functional groups, and is also doped with heteroatoms. These defects and doping sites endow graphene with unique electrochemical activities: for example, introduced vacancy defects can serve as active sites for sodium ion adsorption / intercalation, increasing reversible sodium storage capacity; heteroatom doping alters the electronic structure of graphene, improving its electronic conductivity, and can interact with electrolyte decomposition products to regulate SEI composition. Furthermore, the presence of heteroatoms can participate in and influence SEI film formation during the first charge-discharge process, making the generated SEI more stable and dense. This invention uniformly loads the aforementioned defective graphene material onto the surface of hard carbon anode particles through solution coating or blending, or directly mixes it with a hard carbon precursor and then carbonizes it to generate a composite carbon material, thereby constructing a sandwich-like interface structure of hard carbon particles, defective graphene coating, and electrolyte.

[0011] The structural defects include at least one of vacancy defects and edge defects; the heteroatom doping includes one or more of nitrogen doping, boron doping, oxygen doping, and sulfur doping, with a doping concentration of 0.5 at% to 5 at%.

[0012] Furthermore, the thickness of the defective graphene coating layer is 1 to 5 graphene sheets; the specific surface area of ​​the defective graphene is 100 m². 2 / g~300m 2 / g; the content of surface oxygen functional groups in the surface carbon atoms of the defective graphene is 1at%~10at.

[0013] Furthermore, the hard carbon anode material also includes MXene material or nitrogen-doped carbon material; The MXene material is selected from Ti3C2T. x Two-dimensional materials of transition metal carbides / nitrides.

[0014] Furthermore, the mass ratio of the hard carbon particles to the defective graphene coating layer is 100:(1~10); The hard carbon particles have a particle size of 5μm to 20μm and an interlayer spacing of 0.36nm to 0.40nm.

[0015] The above-mentioned method for preparing a hard carbon anode material based on heteroatom-doped defect graphene includes the following steps: S1: Preparation of defective graphene materials: S2: Preparation of hard carbon particles; S3: The defective graphene obtained in step S1 and the hard carbon particles obtained in step S2 are mixed in a solvent, and the solvent is removed after ultrasonic dispersion and stirring to obtain a composite precursor. S4: Anneal the composite precursor obtained in step S3 under an inert atmosphere to obtain a hard carbon anode material coated with defective graphene.

[0016] Further, step S1 includes: preparing graphene using chemical vapor deposition or redox methods; and then introducing structural defects and / or heteroatom doping into the graphene through at least one of the following methods: a. Plasma treatment, including oxygen or argon, for 5 to 300 seconds, to introduce vacancy defects and oxygen-containing functional groups; b. Rapid thermal annealing, including 700℃~900℃, for 25~35 seconds, introduces edge defects; c. In-situ doping: introducing nitrogen-containing or boron-containing precursors during CVD growth; Preferably, the nitrogen-containing precursor is ammonia or pyridine, and the boron-containing precursor is boron trichloride.

[0017] The in-situ doping method involves introducing a nitrogen-containing precursor or a boron-containing precursor during the chemical vapor deposition growth process. The nitrogen-containing precursor is ammonia or pyridine, and the boron-containing precursor is boron trichloride.

[0018] Further, step S2, preparing hard carbon particles, includes carbonizing the carbon source precursor at 600℃~1200℃ under an inert atmosphere to obtain hard carbon particles. The carbon source precursor mentioned in step S2 is one or more of glucose, lignin, starch, cellulose, or sucrose; Furthermore, in step S3, the defective graphene obtained in step S1 and the hard carbon particles obtained in step S2 are in a mass ratio of 1:(10~100). The solvent mentioned in step S3 is water, ethanol, or N-methylpyrrolidone; the solvent removal method is vacuum filtration, spray drying, or rotary evaporation. In step S4, the annealing temperature is 400~600℃ and the time is 1~3 hours.

[0019] The application of the hard carbon anode material based on heteroatom-doped defective graphene prepared by the above-mentioned preparation method of hard carbon anode material based on heteroatom-doped defective graphene in sodium-ion batteries, wherein the hard carbon anode material serves as the anode active material of sodium-ion batteries.

[0020] Compared with existing technologies, the hard carbon anode material based on heteroatom-doped defect graphene and its preparation method described in this invention have the following advantages: 1. The present invention improves the first-week efficiency by preferentially reacting the defective graphene coating with the electrolyte during the first charge and discharge of the battery, forming a dense and uniform organic / inorganic composite SEI film. This coating isolates the hard carbon surface from the electrolyte, significantly reducing irreversible sodium consumption caused by direct contact between exposed hard carbon and the electrolyte. The defective graphene covers the surface of the hard carbon particles and reacts with the electrolyte decomposition products during the first sodium intercalation process to form a double-layered SEI structure. Due to the presence of graphene, the SEI is denser and more firmly attached, effectively reducing the first irreversible capacity loss. At the same time, heteroatoms in graphene (such as N, B, etc.) can affect and regulate the component ratio of the SEI (e.g., promoting the generation of inorganic components), thereby improving the stability and ionic conductivity of the SEI film. In the embodiments of the present invention, the first-week coulombic efficiency of the hard carbon anode modified with defective graphene can be increased to about 90%, which is significantly higher than the level of about 78-80% for the unmodified hard carbon anode, as measured under the conditions of conventional carbonate electrolyte + 2% FEC additive. This indicates that the present invention significantly reduces irreversible sodium loss during the first charge and discharge cycle.

[0021] 2. The present invention enhances interface stability. The graphene coating, acting as a flexible supporting protective film, effectively buffers the volume changes of hard carbon particles during sodium insertion / deintercalation, preventing pulverization of the anode material and delamination at the electrode / electrolyte interface. The graphene sheet firmly adheres to the hard carbon surface, forming a protective layer. Due to the strong bonding between the defective graphene and the hard carbon surface, the SEI film generated at the interface is not easily peeled off during repeated charge-discharge cycles. Unmodified hard carbon anodes develop surface cracks and SEI film breakage and peeling after several cycles, while the modified anode of the present invention maintains an intact particle structure and continuous graphene coating after cycling under the same conditions. Electrochemical cycle life test results also confirm the improved interface stability. The modified anode of the present invention retains ≥90% capacity retention after 500 cycles at 1C current density, significantly better than the approximately 80% capacity retention of the unmodified hard carbon control group under the same conditions. Therefore, the defective graphene coating effectively inhibits the pulverization of the active material and repeated SEI breakage and regeneration, improving the long cycle life.

[0022] 3. The present invention improves rate performance. The defective graphene possesses extremely high conductivity and forms an interconnected conductive network and two-dimensional interlayer channels on the surface of hard carbon particles, providing a rapid path for electron conduction and sodium ion diffusion. On one hand, the presence of graphene nanosheets reduces the contact resistance between hard carbon particles; on the other hand, the voids, defects, and wrinkles on the graphene sheets facilitate electrolyte penetration, making it easier for sodium ions to enter the particle interior. Within a discharge rate range of 0.1C to 5C, the modified anode of the present invention exhibits higher specific capacity and better reversibility. Specifically, it retains more than 70% of its initial capacity even at a high rate of 5C, while the capacity of ordinary unmodified hard carbon rapidly decays to less than 50% at 5C. Furthermore, heteroatom doping (such as the introduction of nitrogen atoms) can improve the material's resistance to concentration polarization and maintain coulombic efficiency at high rates. Tests in Example 2 of the present invention show that the coulombic efficiency of the modified anode remains almost 99% at all rates, far exceeding the level of approximately 95% for the unmodified anode at high rates. These results demonstrate that the present invention significantly enhances the kinetic performance of the electrode, enabling efficient and reversible sodium insertion / extraction even under high current charging and discharging.

[0023] 4. The present invention improves reversible capacity because, in addition to serving as a protective coating interface, the defective graphene itself can also contribute a certain amount of sodium storage capacity. Its surface functional groups and structural defect sites can reversibly bond Na... +This allows graphene to function similarly to the active sites of hard carbon. Furthermore, the doping modification of graphene also affects the microstructure of the hard carbon matrix: the introduction of dopants may slightly expand the interlayer spacing of the hard carbon graphite and induce the formation of more disordered layers and defects, thus facilitating the inclusion of more sodium ions. The combined effect of these two aspects improves the reversible capacity of the modified anode material of this invention. At a current density of 0.1C, the initial discharge specific capacity of the modified anode reaches approximately 280–300 mAh / g, a significant improvement compared to unmodified hard carbon (typically <250 mAh / g). The modified sample exhibits a higher initial discharge capacity and a more stable voltage plateau, with a coulombic efficiency approaching 90%, while the initial coulombic efficiency of the unmodified sample is only about 78.5%. With cycling, the reversible capacity of the modified anode remains excellent, far exceeding that of the unmodified control. This demonstrates that the introduction of defective graphene improves the overall sodium ion storage capacity of the electrode.

[0024] 5. This invention achieves effective suppression of the initial side reaction of the anode and simultaneous optimization of kinetic performance by constructing a hard carbon anode, a defective graphene coating, and a stable SEI sandwich interface structure, supplemented by heteroatom doping. This strategy innovatively combines surface coating and internal doping modification methods, significantly improving the first-cycle efficiency, rate performance, and cycle life of hard carbon materials without sacrificing their high specific capacity advantage. It overcomes the limitations of any single modification method and has significant novelty and inventiveness.

[0025] 6. This invention demonstrates excellent feasibility and industrialization prospects in terms of material selection and process. The raw materials for each component are widely available and inexpensive. Defective graphene can be mass-produced from inexpensive graphite oxides through methods such as chemical reduction or plasma treatment; hard carbon materials can be obtained by carbonizing biomass precursors such as glucose and lignin, making the raw materials green and renewable. The entire composite preparation process employs conventional processes such as solution coating, ultrasonic mixing, and heat treatment, which can be easily integrated into existing battery electrode manufacturing processes. Therefore, this invention not only verifies performance improvements on a laboratory scale but also possesses the conditions for scale-up preparation and industrial application. In summary, this invention provides a novel technical route for preparing high-performance, long-life sodium-ion battery anode materials, which is expected to promote the commercialization of sodium-ion batteries. Attached Figure Description

[0026] The accompanying drawings, which form part of this invention, are used to provide a further understanding of the invention. The illustrative embodiments of the invention and their descriptions are used to explain the invention and do not constitute an undue limitation of the invention. In the drawings: Figure 1 XPS characterization of the defective graphene-coated hard carbon anode particles proposed in this invention (a is the full spectrum, b is the C1s peak). Figure 2This is a schematic diagram of the structure of the defective graphene-coated hard carbon anode particles proposed in this invention. Figure 3 This is a schematic diagram of the mechanism for the formation of a stable SEI film in the modified hard carbon anode of the present invention (1 is electrolyte wetting, 2 is decomposition and deposition, 3 is inner SEI formation, and 4 is outer SEI growth). Figure 4 The graphs show the performance comparison of different negative electrodes after the first cycle and long cycle (a is the comparison of the first charge and discharge curves, b is the comparison of the capacity retention rate after 500 cycles at 1C). Figure 5 This is a rate performance curve of the defective graphene-modified hard carbon anode of the present invention. Figure 6 XPS spectra of the SEI composition on the surface of the modified and unmodified anodes after the first cycle are compared (a is the F1s peak, corresponding to the content of inorganic fluoride in the SEI, and b is the C1s peak). Detailed Implementation

[0027] It should be noted that, unless otherwise specified, the embodiments and features described in the present invention can be combined with each other.

[0028] The present invention will now be described in detail with reference to the accompanying drawings and embodiments.

[0029] Raw material preparation: First, defective graphene and hard carbon materials are prepared. The graphene precursor is obtained by oxidizing natural graphite using a modified Hummers method to produce a graphene oxide (GO) suspension. This GO suspension is then pyrolyzed at 300℃ or chemically reduced with a reducing agent to obtain reduced graphene oxide (rGO) with a certain defect concentration. To further increase the defect density in the graphene, the obtained rGO can be post-treated, for example, by using low-power plasma (such as O2 plasma treatment for 5 minutes) to introduce additional oxygen-containing functional groups and a small number of vacancy defects onto its surface. Simultaneously, heteroatom doping can be introduced during the preparation process. Urea solution is added to the GO suspension, stirred evenly, and then calcined at 800℃ under a nitrogen atmosphere for 1 hour to obtain nitrogen-doped defective graphene (N-rGO). The specific surface area of ​​the defective graphene obtained by the above process can reach 100–300 m². 2 / g, with a total oxygen-containing functional group (carboxyl, hydroxyl, etc.) content of approximately 5–10% and a nitrogen doping content of approximately 2 at%. XPS characterization shows that its carbon framework contains a large amount of sp. 2 Carbon defect sites were incorporated, along with bound nitrogen species such as pyridine nitrogen and graphitic nitrogen. This defective graphene possesses abundant electrochemical active sites and high electronic conductivity.

[0030] Hard carbon materials can be prepared using biomass precursors: carbon sources such as glucose and lignin are carbonized at 900℃ under an inert atmosphere to obtain amorphous hard carbon microparticles. The resulting hard carbon particles have a D50 diameter of approximately 10µm, and XRD analysis shows that their graphite (002) interlayer spacing is approximately 0.37nm, exhibiting a certain degree of graphitization and containing a microporous structure. Hard carbon itself generally contains a small amount of intrinsic defects and heteroatoms (total content <1%). When necessary, hard carbon can be surface pretreated to increase functional groups, thereby enhancing its bonding with graphene. For example, concentrated nitric acid can be used to oxidize hard carbon powder, introducing oxygen-containing functional groups such as carboxyl and hydroxyl groups onto its surface. Such surface-modified hard carbon is more likely to form a strong interfacial bond with graphene.

[0031] Defective graphene-coated hard carbon: The prepared hard carbon powder was added to a pre-mixed N-rGO suspension, with the mass ratio of hard carbon to graphene controlled at 100:5. Ultrasonic dispersion was performed for 30 minutes to ensure complete exfoliation and uniform adhesion of the graphene sheets to the surface of each hard carbon particle, forming a hard carbon / graphene suspension mixture. The solvent was then removed by vacuum filtration or spray drying to obtain a hard carbon precursor powder with a graphene coating. Next, the precursor was annealed at 500°C for 2 hours under an inert atmosphere. This heat treatment step enhances the bonding strength between graphene and hard carbon, while removing residual solvent and organic impurities. After annealing, the resulting defective graphene-coated hard carbon composite material was a grayish-black powder.

[0032] Figure 1 The XPS characterization results of the defective graphene-coated hard carbon anode particles proposed in this invention are shown. Figure 1 The XPS full spectrum (a) clearly shows the characteristic peaks of C1s, N1s, and O1s, confirming that nitrogen and oxygen elements have been successfully doped into the graphene structure. These results collectively demonstrate that the prepared graphene contains abundant structural defects and heteroatom doping sites, providing the necessary chemically active sites and electrochemical functions for its use as a hard carbon anode interface control layer.

[0033] Figure 2 This is a schematic diagram of a hard carbon anode particle with defective graphene coating. The surface of the hard carbon particle is coated with a thin layer of defective graphene. The graphene layer contains several structural defects (such as pores and broken edges) and doped heteroatoms. Raman's I... D / I G The value is 1.05 to 1.35, preferably 1.2. The defective graphene layer adheres firmly to the hard carbon surface through chemical bonding, forming a stable interfacial protective layer.

[0034] Figure 3This is a schematic diagram illustrating the mechanism of stable SEI film formation in the modified hard carbon anode of this invention. The diagram shows a defective graphene coating covering the surface of the hard carbon particles. During the initial sodium intercalation process, the graphene coating reacts with the electrolyte decomposition products, forming a bilayer solid electrolyte interphase (SEI) film in situ at the interface: the inner SEI layer, closely adhering to the hard carbon surface, is rich in inorganic components such as NaF, while the outer SEI layer is a polycarbonate-based organic film. Due to the presence of the graphene coating, the formed SEI film is dense, uniform, and firmly attached to the anode surface, thereby effectively improving the stability of the interface.

[0035] In other alternative embodiments, MXene two-dimensional materials or other conductive phases may be further introduced into the composite structure of the present invention.

[0036] A certain amount of MXene (such as Ti3C2T) was added to the above graphene suspension. x MXene nanosheets, along with graphene, serve as a coating material. MXene possesses metallic conductivity and abundant surface functional groups; its introduction can further enhance the interfacial electron / ion transport capability and mechanical stability of the composite anode. Conductive nitrogen-doped carbon nanomaterials (such as nitrided carbon nanotubes or carbon nanofibers) can also be added between the hard carbon particles and graphene to construct a sandwich-like composite electrode architecture. These variations are extensions of the present invention and can further improve interfacial stability and rate performance.

[0037] Electrode preparation and electrochemical testing The prepared hard carbon / defect graphene composite powder was mixed with conductive agent SuperP and binder PVDF at a mass ratio of 80:10:10 until homogeneous. An appropriate amount of N-methylpyrrolidone (NMP) solvent was added and stirred to form a uniform slurry. The slurry was evenly coated onto a copper foil current collector and vacuum dried at 80°C for 12 hours. The dried slurry was then cut into 14mm diameter discs to serve as the negative electrode. A sodium metal sheet was used as the counter electrode, and a glass fiber membrane as the separator. A CR2032 coin cell was assembled in a glove box. The electrolyte was 1M NaPF6 dissolved in a carbonate mixture EC / DMC (1:1 volume ratio), with 2% by mass of fluoroethylene carbonate (FEC) added as a film-forming additive. This electrolyte formulation typically has a first-week coulombic efficiency of only about 78% in the unmodified hard carbon system; its improvement effect will be observed in the modified negative electrode of this invention. The assembled coin cells were allowed to stand for 12 hours to fully wet the electrodes.

[0038] Electrochemical performance of the battery was tested at room temperature (25°C). First, the battery underwent two constant-current charge-discharge pre-cycles at a current density of 0.1C (approximately 25 mA / g) to form an SEI film. Subsequently, it was cycled 10 times each at discharge rates of 0.1C, 0.2C, 0.5C, 1C, 2C, and 5C, before returning to 0.1C to test recovery capacity and evaluate rate performance and reversibility. Constant-current charge-discharge curves and corresponding capacity and coulombic efficiency data were recorded at each rate. Simultaneously, a long-cycle life test was conducted at 1C: 500 consecutive charge-discharge cycles, with capacity decay recorded every 50 cycles. Electrochemical impedance spectroscopy (EIS) measurements were also performed periodically during the tests (in the frequency range of 100 kHz–0.1 Hz) to monitor charge transfer resistance (Rc) after the first cycle and after multiple cycles. ct The evolution of interfacial film impedance was studied. All comparative control samples in the tests were pure hard carbon anode batteries without graphene modification, and all other conditions (electrolyte, additives, test protocol, etc.) were the same as those for the modified samples.

[0039] Example 1: Improvement in Coulomb efficiency during the first week The constant current charge-discharge performance of the unmodified hard carbon anode and the defective graphene-modified hard carbon anode of this invention were tested in the first cycle. The test conditions were: 0.1C current density (about 25mA / g) and voltage window 0.01–2.5V.

[0040] The unmodified hard carbon anode exhibits significant irreversible capacity loss during the first charge-discharge cycle. Its initial charge specific capacity is 312 mAh / g, the initial discharge specific capacity is 245 mAh / g, and the initial irreversible capacity loss reaches 67 mAh / g, corresponding to a first-cycle coulombic efficiency of only 78.5%. A distinctly sloping low-voltage plateau is observed in the first discharge curve, ranging from 0.05 to 0.2 V, indicating strong electrolyte decomposition side reactions and SEI film formation on the electrode surface. Its average first-cycle discharge voltage is approximately 0.42 V, with a charge-discharge voltage hysteresis of approximately 0.31 V. In contrast, the defective graphene-modified hard carbon anode of this invention exhibits significantly improved initial electrochemical behavior. The modified anode's initial charge specific capacity increases to 330 mAh / g, the initial discharge specific capacity reaches 300 mAh / g, and the irreversible capacity loss is only about 30 mAh / g, corresponding to a first-cycle coulombic efficiency of 90.9%. Its first discharge curve shows a more stable low-voltage plateau and reduced polarization, indicating more controllable interfacial reactions. The modified negative electrode has an average discharge voltage of approximately 0.47V during the first cycle, and the charge / discharge voltage decreases to approximately 0.18V with hysteresis.

[0041] This indicates that the defective graphene coating and the electrolyte additive FEC work synergistically to rapidly generate a stable SEI film on the hard carbon surface, effectively reducing the irreversible consumption of sodium ions during the first charge and protecting the sodium ion storage sites inside the hard carbon. Therefore, the modified negative electrode exhibits a significantly reduced irreversible capacity loss during the first cycle. Figure 4 Figure a shows a comparison of the first charge-discharge curves of the modified hard carbon anode and the unmodified hard carbon anode of this invention. It can be seen that the modified anode has a higher first-discharge specific capacity and a coulombic efficiency close to 90%, significantly better than the unmodified anode's first-cycle efficiency of only about 78%. Figure 4 b is a bar chart comparing the capacity retention of the two anodes after 500 cycles at a current density of 1C. The capacity retention of the modified anode of this invention is significantly higher than that of the unmodified control group, which clearly demonstrates the effect of defective graphene modification on improving cycle life. Figure 4 The first-cycle charge-discharge curves of the two negative electrodes shown in Figure a also reflect this difference: the first-cycle discharge curve of the modified negative electrode has a larger area and a more stable plateau, with a coulombic efficiency close to 91%, while the first-cycle discharge curve of the unmodified negative electrode shows a large lag and a significant tilt in the voltage plateau, with a coulombic efficiency of less than 80%.

[0042] Example 2: Ratio Performance Comparison The discharge capacity and coulombic efficiency of modified and unmodified hard carbon anodes were tested at different rates (0.1C to 5C). Figure 5 As shown, the curves illustrate the specific capacity changes of the modified and unmodified hard carbon anodes at different discharge rates from 0.1C to 5C. The modified anode of this invention maintains a high specific capacity and near 100% coulombic efficiency at all discharge rates. Specifically, at a high discharge rate of 5C (approximately 5 A / g), it retains more than 70% of its initial capacity, and the capacity is almost completely recovered when returning to 0.1C, demonstrating excellent rate performance and reversibility. In contrast, the ordinary hard carbon anode rapidly decays to less than 50% of its initial capacity at high rates, and its coulombic efficiency decreases significantly at high rates.

[0043] At 0.1C, the discharge capacity of the unmodified hard carbon electrode is approximately 250 mAh / g, while the modified electrode of this invention reaches approximately 280 mAh / g. When the rate is increased to 1C, the capacity of the unmodified sample decreases to approximately 160 mAh / g, while the modified sample remains at approximately 200 mAh / g. Further increasing to a high-rate discharge of 5C, the capacity of the unmodified hard carbon electrode drops to only about 100 mAh / g (equivalent to 40% of the initial capacity), while the modified sample can still output a capacity of no less than 150 mAh / g, approximately 75% of the initial capacity. More remarkably, the coulombic efficiency of the modified electrode is close to 99% at all rates, while the coulombic efficiency of the unmodified hard carbon electrode drops to approximately 95% at high rates, indicating that the unmodified electrode undergoes more side reactions or irreversible losses under rapid charge-discharge conditions. These results clearly demonstrate that this invention, through defective graphene modification, significantly improves the sodium ion insertion / extraction kinetics and reversibility of the hard carbon anode at high rates, and reduces polarization. This is consistent with the performance trend of nitrogen-doped hard carbon materials reported in the literature: for example, some nitrogen-doped hard carbon samples achieved an efficiency of 84% in the first cycle and a capacity retention rate of over 91% after 100 cycles at 0.2C. In this invention, graphene coating is further added on the basis of nitrogen doping, which significantly improves both the first efficiency and high-rate performance.

[0044] Example 3: Long-cycle stability test Long cycle life tests were conducted on the unmodified hard carbon anode and the defective graphene-modified hard carbon anode of this invention under constant current 1C rate conditions (approximately 250 mA / g), with a voltage range of 0.01–2.5V and a cycle count of 500.

[0045] The unmodified hard carbon anode exhibits rapid capacity decay during cycling. Its initial reversible capacity is approximately 248 mAh / g, decreasing to 218 mAh / g after 50 cycles, with a capacity retention of approximately 87.9%. After 100 cycles, the capacity further decreases to 198 mAh / g; after 200 cycles, it is only 186 mAh / g, with a capacity retention of 75.0%; and by the end of 500 cycles, the discharge capacity is only 145 mAh / g, with a capacity retention of only 58.5%. Meanwhile, its average coulombic efficiency is approximately 98.2% in the first 100 cycles, then gradually decreases, dropping to around 96.5% near 500 cycles. During cycling, the voltage plateau gradually tilts, with the charge-discharge voltage difference increasing from the initial 0.19V to 0.43V, indicating a continuous increase in interfacial impedance and intensified polarization. In contrast, the defective graphene-modified hard carbon anode of this invention exhibits excellent cycling stability. Its initial reversible capacity was approximately 302 mAh / g, which remained at 287 mAh / g after 50 cycles, representing a capacity retention of approximately 95.0%; after 100 cycles, the capacity was 281 mAh / g; after 200 cycles, it remained at 272 mAh / g, representing a capacity retention of approximately 90.1%; even after 500 long cycles, the discharge capacity still reached over 274 mAh / g, with a capacity retention of as high as 90.7%. Throughout the cycling process, the coulombic efficiency remained between 99.2% and 99.8%, without a significant downward trend.

[0046] After the experiment, the battery was disassembled and observed, and no sodium dendrite deposition was found on the modified negative electrode surface. This proves that the defective graphene coating introduced in this invention greatly stabilizes the SEI film and protects the active material particles from crushing and shedding during repeated volume changes, significantly reducing the gradual loss of active material. The negative electrode material of this invention exhibits a capacity retention rate far exceeding that of conventional hard carbon negative electrodes after hundreds of charge-discharge cycles, and is superior to many reported values ​​in the literature. Therefore, through the interface modification strategy of this invention, the cycle life of the sodium-ion battery negative electrode is extended several times over.

[0047] Example 4: Analysis of Interface Impedance and SEI Characteristics The electrochemical impedance spectroscopy (EIT) of modified and unmodified hard carbon anodes was measured after the first cycle and after multiple cycles to compare the differences in interfacial film impedance. The charge transfer impedance Ri of the unmodified hard carbon anode after the formation of the SEI film during the first charge-discharge cycle was measured. ct It is approximately 240Ω, while the R of the modified negative electrode of this invention... ct The Ω was reduced to approximately 120Ω, a 50% decrease. This indicates that the composite SEI film generated by the defective graphene coating has higher ionic / electronic conductivity and smoother interfacial transport. After 100 cycles, the R of the unmodified hard carbon anode... ctThe further increase to over 400Ω suggests that its SEI film may continue to thicken or undergo rupture and regeneration, leading to interface deterioration; conversely, the Rct of the modified hard carbon anode only increased slightly to about 130Ω, remaining basically stable.

[0048] Figure 6 XPS spectra of the SEI composition on the surface of the modified and unmodified anodes after the first cycle are compared. a) shows the F1s peak, corresponding to the content of inorganic fluoride components in the SEI; it can be seen that the NaF peak intensity of the modified anode is significantly higher than that of the unmodified anode, indicating a higher content of dense inorganic components in the SEI of the modified anode. b) shows the C1s peak; it can be seen that the polycarbonate organic component peaks are more prominent in the SEI of the unmodified anode, while the modified anode, due to the presence of the graphene coating, has its organic components suppressed, resulting in a smaller carbonate peak area in the C1s spectrum. These XPS results demonstrate that the defective graphene coating of this invention induces the formation of a stable SEI film rich in inorganic components. This SEI film exhibits better thermal stability and mechanical strength, which is beneficial for long-term cycling.

[0049] Figure 6 XPS analysis results also support this, showing strong NaF and other inorganic peaks detected in the SEI of the modified anode after the first cycle, while the SEI of the unmodified anode was dominated by organic carbonates with a higher content, indicating that the former's SEI is more dense and inorganic, while the latter's SEI is more loose and organic. These differences indicate that the graphene coating of this invention promotes the formation of a high-quality SEI, keeping the interfacial impedance at a low level. By forming a stable SEI with the graphene anode through appropriate electrolyte formulation, cycle stability and rate performance can be significantly improved. This invention cleverly achieves similar or even better results without changing the electrolyte through a material surface pre-modification method.

[0050] The data from the above embodiments verify that the defective graphene-modified hard carbon anode material prepared in this invention exhibits significant performance improvements compared to unmodified hard carbon. Specifically, the first-cycle coulombic efficiency is increased by approximately 15 percentage points, cycle life is more than doubled, and high-rate capacity is increased by more than 50%. These performance leaps stem from the dual optimization effect of defective graphene materials on the hard carbon anode in terms of interface stabilization and ion diffusion channel construction: on the one hand, the graphene coating acts as a protective barrier, effectively suppressing electrolyte decomposition reactions and excessive SEI growth; on the other hand, graphene, as a functional conductive additive, improves the conductive framework of the anode and increases sodium storage active sites, resulting in a more complete and faster overall electrode reaction. Therefore, the technical solution of this invention provides a novel approach and tool for the design of next-generation high-performance sodium-ion battery anodes. Furthermore, this solution can be combined with other modules of the Thunderbird Super Battery platform to construct an integrated, multifunctional energy storage device system in the future, unlocking greater application potential.

[0051] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A hard carbon anode material based on heteroatom-doped defect graphene, characterized in that: include: Hard carbon particles; And the defective graphene coating layer covering the surface of the hard carbon particles; The defective graphene coating contains structural defects and heteroatom doping.

2. The hard carbon anode material based on heteroatom-doped defect graphene according to claim 1, characterized in that: The structural defects include at least one of vacancy defects and edge defects; the heteroatom doping includes one or more of nitrogen doping, boron doping, oxygen doping, and sulfur doping, with a doping concentration of 0.5 at% to 5 at%.

3. The hard carbon anode material based on heteroatom-doped defect graphene according to claim 1, characterized in that: The thickness of the defective graphene coating is 1 to 5 graphene sheets; the specific surface area of ​​the defective graphene is 100 m². 2 / g~300m 2 / g; the content of surface oxygen functional groups in the surface carbon atoms of the defective graphene is 1at%~10at.

4. The hard carbon anode material based on heteroatom-doped defect graphene according to claim 1, characterized in that: The hard carbon anode material also includes MXene material or nitrogen-doped carbon material; The MXene material is selected from Ti3C2T. x Two-dimensional materials of transition metal carbides / nitrides.

5. The hard carbon anode material based on heteroatom-doped defect graphene according to claim 1, characterized in that: The mass ratio of the hard carbon particles to the defective graphene coating is 100:(1~10); The hard carbon particles have a particle size of 5μm to 20μm and an interlayer spacing of 0.36nm to 0.40nm.

6. A method for preparing a hard carbon anode material based on heteroatom-doped defect graphene according to any one of claims 1 to 5, characterized in that, Includes the following steps: S1: Preparation of defective graphene materials: S2: Preparation of hard carbon particles; S3: The defective graphene obtained in step S1 and the hard carbon particles obtained in step S2 are mixed in a solvent, and the solvent is removed after ultrasonic dispersion and stirring to obtain a composite precursor. S4: Anneal the composite precursor obtained in step S3 under an inert atmosphere to obtain a hard carbon anode material coated with defective graphene.

7. The method for preparing a hard carbon anode material based on heteroatom-doped defect graphene according to claim 6, characterized in that: Step S1 includes: preparing graphene using chemical vapor deposition or redox methods; and then introducing structural defects and / or heteroatom doping into the graphene through at least one of the following methods: a. Plasma treatment, including oxygen or argon, for 5 to 300 seconds, to introduce vacancy defects and oxygen-containing functional groups; b. Rapid thermal annealing, including 700℃~900℃, for 25~35 seconds, introduces edge defects; c. In-situ doping: introducing nitrogen-containing or boron-containing precursors during CVD growth; Preferably, the nitrogen-containing precursor is ammonia or pyridine, and the boron-containing precursor is boron trichloride.

8. The method for preparing a hard carbon anode material based on heteroatom-doped defect graphene according to claim 6, characterized in that: Step S2, preparing hard carbon particles, involves carbonizing a carbon source precursor at 600℃~1200℃ under an inert atmosphere to obtain hard carbon particles. The carbon source precursor mentioned in step S2 is one or more of glucose, lignin, starch, cellulose or sucrose.

9. The method for preparing a hard carbon anode material based on heteroatom-doped defect graphene according to claim 6, characterized in that: In step S3, the defective graphene obtained in step S1 and the hard carbon particles obtained in step S2 are in a mass ratio of 1:(10~100); The solvent mentioned in step S3 is water, ethanol, or N-methylpyrrolidone; the solvent removal method is vacuum filtration, spray drying, or rotary evaporation. In step S4, the annealing temperature is 400~600℃ and the time is 1~3 hours.

10. The application of a hard carbon anode material based on heteroatom-doped defect graphene prepared by any one of claims 1 to 5 or any one of claims 7 to 9 in a sodium-ion battery, characterized in that, The hard carbon anode material is used as the anode active material in sodium-ion batteries.

Citation Information

Patent Citations

  • Graphene-based sodium ion battery

    CN106785008A

  • Biomass derived hard carbon / graphene sodium-ion battery negative electrode material and preparation method thereof

    CN108777303A

  • Preparation method of oxygen-enriched defective sodium titanate / graphene composite cathode material

    CN109686961A

  • Pre-sodium-modified graphene negative pole piece, preparation method thereof and sodium ion battery

    CN113178548A

  • Nitrogen-doped hard carbon sodium ion battery negative electrode material and preparation method thereof

    CN114275762A